Physical oceanography during Alkor cruise AL598 - Listmann, Luisa (PANGAEA, 2024)
This data set comprises unprocessed CTD data collected during the RV ALKOR cruise AL598 conducted in July/August 2023 (27th of July to 6th of August) in the Western Baltic Sea by the University of Hamburg. The cruise was part of the 5-year MARSYS teaching cruise program of the University of Hamburg GFP20-1_047. The cruises are designed to train students in sampling methods targeting the different compartments of a marine ecosystem. The CTD data was obtained directly from the Sea & Sun Technology software. No quality control of the data has been done.
Keywords: Baltic Sea; Field measurements; RV ALKOR; summer; Teaching cruise